(untitled) (Higher Education Politics and Economics, 2020)
Community colleges in the United States have historically held a unique position within the system of higher education because of three characteristics. These characteristics include their doctrine of open access, their consistent affordability in comparison to other higher education options, and courses that are directly applicable to the workforce. However, over the years, contradictions have arisen that compromise the practice of these ideals. Focusing on three policy priorities, this analysis determines how effective community colleges are today in offering students an education that is accessible, applicable to the labor market, and affordable. The concluding points include predictions of what the future of community colleges looks like within the next twenty years.